Changes in the Characteristics and Levels of Comorbidity Among New Patients Into Methadone Maintenance Treatment Program in British Columbia During Its Expansion Period From 1998–2006. (18th June 2013) - Sharif, Behnam; Nosyk, Bohdan; Sun, Huiying; Marsh, David C.; Anis, Aslam
Abstract : We described the changing characteristics and comorbidity levels of new patients into Methadone maintenance treatment (MMT) program in British Columbia, Canada, during its expansion period of 1998–2006. Analyses used administrative data. Generalized regression models were applied using Charlson Comorbidity Index (CCI) and Chronic Disease Score (CDS) as outcomes. 12, 615 individuals initiated MMT during 1998–2006, while their odds of having moderate CCI (1 ≤ CCI ≤ 4) and mean CDS increased by 60% and 11%, respectively, after adjusting for confounders. MMT entrants were presented with progressively higher levels of comorbidity, independent of other characteristics. Future MMT policies should address higher levels of comorbidity among new patients.